This preview has intentionally blurred sections. Sign up to view the full version.
View Full DocumentThis preview has intentionally blurred sections. Sign up to view the full version.
View Full DocumentThis preview has intentionally blurred sections. Sign up to view the full version.
View Full Document
Unformatted text preview: Applied Econometrics William Greene Department of Economics Stern School of Business Applied Econometrics 5. Regression Algebra and a Fit Measure The Sum of Squared Residuals b minimizes e ′ e = ( y  Xb ) ′ ( y  Xb ). Algebraic equivalences, at the solution b = ( X ′ X )1 X ′ y e’e = y ′ e (why? e’ = y’ – b’X’ ) e ′ e = y ′ y  y’Xb = y ′ y  b ′ X ′ y = e ′ y as e ′ X = (This is the F.O.C. for least squares.) Minimizing e ’ e Any other coefficient vector has a larger sum of squares. A quick proof: d = the vector, not b u = y  Xd . Then, u ′ u = ( y  Xd ) ′ ( y Xd ) = [ y  Xb  X ( d  b )] ′ [ y  Xb  X ( d  b )] = [ e  X ( d  b )] ′ [ e  X ( d  b )] Expand to find u ′ u = e ′ e + ( d b ) ′ X ′ X ( d b ) > e ′ e Dropping a Variable An important special case. Suppose [ b ,c]=the regression coefficients in a regression of y on [ X , z ]and d is the same, but computed to force the coefficient on z to be 0. This removes z from the regression. (We’ll discuss how this is done shortly.) So, we are comparing the results that we get with and without the variable z in the equation. Results which we can show: Dropping a variable(s) cannot improve the fit  that is, reduce the sum of squares. Adding a variable(s) cannot degrade the fit  that is, increase the sum of squares. The algebraic result is on text page 31. Where u = the residual in the regression of y on [ X,z ] and e = the residual in the regression of y on X alone, u’u = e ′ e – c 2 ( z * ′ z *) ≤ e ′ e where z * = M X z . This result forms the basis of the NeymanPearson class of tests of the regression model. The Fit of the Regression “Variation:” In the context of the “model” we speak of variation of a variable as movement of the variable, usually associated with (not necessarily caused by) movement of another variable. Total variation = = y ′ M y . M = I – i(i’i)1 i’ = the M matrix for X = a column of ones....
View
Full
Document
This note was uploaded on 06/20/2011 for the course ECON 803 taught by Professor Pp during the Spring '11 term at Thammasat University.
 Spring '11
 PP
 Econometrics

Click to edit the document details